2018
DOI: 10.1080/02626667.2018.1487560
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of soil moisture in calibration of rainfall–runoff models: two case studies

Abstract: Streamflow modelling results from the GR4H and PDM hydrological models were evaluated in two Australian sub-catchments, using (1) calibration to streamflow and (2) joint-calibration to streamflow and soil moisture. Soil moisture storage in the models was evaluated against soil moisture observations from field measurements. The PDM had the best performance in terms of both streamflow and soil moisture estimations during the calibration period, but was outperformed by GR4H during validation. It was also shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In turn, snow persistence has been found to produce more rapid snowmelt to induce soil saturation (Trujillo & Molotch, 2014), after which water can move vertically as recharge or laterally through the soil zone as interflow to promote more streamflow (Barnhard et al, 2020; Barnhart et al, 2016). Lateral movement of water is largely a function of soil storage and water holding capacity (Xiao et al, 2019) and initial soil moisture content, such that soil moisture observations can improve streamflow forecasts (Crow et al, 2018; Mahanama et al, 2012; Shahrban et al, 2018). Use of LiDAR snow observations informs where snow ends up, not necessarily where it fell.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, snow persistence has been found to produce more rapid snowmelt to induce soil saturation (Trujillo & Molotch, 2014), after which water can move vertically as recharge or laterally through the soil zone as interflow to promote more streamflow (Barnhard et al, 2020; Barnhart et al, 2016). Lateral movement of water is largely a function of soil storage and water holding capacity (Xiao et al, 2019) and initial soil moisture content, such that soil moisture observations can improve streamflow forecasts (Crow et al, 2018; Mahanama et al, 2012; Shahrban et al, 2018). Use of LiDAR snow observations informs where snow ends up, not necessarily where it fell.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used ground‐based or alternatively remote sensing products or their combination as such additional information on hydrologic processes. Soil moisture (Kundu et al, 2017; Kunnath‐Poovakka et al, 2016; Parajka et al, 2006; Rajib et al, 2016; Shahrban et al, 2018), evapotranspiration (Gui et al, 2019; Herman et al, 2018; Immerzeel & Droogers, 2008; Kunnath‐Poovakka et al, 2016), and groundwater level data (Demirel et al, 2019; Seibert, 2000) were often used for model calibration to improve the model's internal consistency. These studies showed the added value of different observations besides runoff, for example, for soil moisture, evapotranspiration, and groundwater levels.…”
Section: Introductionmentioning
confidence: 99%
“…This may be partially due to the use of a simplified soil moisture conceptual model in SWAT, such as a bucket [40]. Shahrban et al [66] also found that a hydrologic model using a bucket concept for soil moisture poorly simulated low-flow conditions relative to a model that used a continuous distribution of soil moisture according to vertical depth. Based on this FDC result, we postulate that RSWAT may have a greater capacity to replicate water partitioning processes than SWAT.…”
Section: Streamflow and Et Predictions At The Watershed Levelmentioning
confidence: 99%